Citotaxonomía comparativa de tres especies de Cichlasoma (Pisces: Cichlidae) nativas de Costa Rica - Salas, Elizabeth (1991)
The karyotype oí three species oí CichlasofM: C. dOllii, C. managwmse and C. friedrichstali were studied. The number of diploid chromosomes is 2n=48 in the fust two species. Their karyotypes are composed of four pairs of meta-submetacentric chromosomes. The arms fundamental number (NF) is 56. C. friedrichstali has three pairs oí me ta-submetacentric chromosomes and 21 pairs of subtelocentric-telocentric chromosomes. This species presents two different diploid numbers, 2n=48 and 2n=47.